IMPLEMENTATION OF THE AGRICULTURAL LAND TRANSFER FUNCTION FOR HOUSING IN SIGI - Rachman, Rahmia; Datupalinge, Suarlan; Ardiansyah, Erlan (Tadulako University, 2020)
Sigi is a region which has an area of 5.196Â , with a population of 229.474 inhabitants. Sigi location of the region is not too far to the capital of Central Sulawesi province, the city of Palu, from year to year growth of people needing somewhere to stay home. Housing developments in Sigi is growing as well. The impact, the development of residential areas in Sigi reduces existing agricultural lands. With the limited land in this area tends to be increased conversion resulting from agricultural land to non-agricultural rapidly and progressively. Agricultural land have been converted to other uses outside the agricultural sector will be very little chance to turn back to agriculture.The problems examined in this study aims to determinehow the implementation of the conversion of agricultural land into housing in Sigi.The results of this study indicate thatÂ agricultural land conversion to non agriculture has frequently occurred in the village of Pombewe, Sigi. Some agricultural land in the village Pombewe much in alihfungsikan into housing, but land is not included in the sustainable food agricultural land, due to be sustainable food agricultural land as well as the requirements and criteria to be set by the Regent.